Doing good when doing well: evidence on real earnings management - Grieser, William; Hadlock, Charles J.; Pierce, Joshua R. (Review of Accounting Studies, 2021)
Abstract We provide evidence on earnings management by exploiting temporary exogenous shocks to utility firms’ sales arising from weather variation. We find that sample firms’ sales are highly sensitive to annual changes in average temperatures in the region where the firm operates, but this sensitivity disappears quickly as one moves down the income statement. This evidence, while indirect, is suggestive of earnings management activities. In search of direct evidence, we study charitable giving decisions by sample firms and uncover a significant positive sensitivity of charitable spending to weather-driven demand shocks, behavior that is highly consistent with the presence of real earnings management efforts. We find no convincing evidence supporting possible alternative explanations for this evidence, but we do find limited support for the presence of a larger giving–weather relation when earnings management incentives are likely to be elevated. If other real decisions with similar characteristics scale proportionally to charitable giving, our findings suggest that the overall magnitude of real earnings management activities could be quite substantial.